The Influence of Promotion and Service Quality on Insurance Policy Purchase Decisions at PT. Tugu Kresna Pratama Bengkulu City - Meliyus Astutiana; Ermy Wijaya; Andriyani Prawitasari (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is the promotion and quality of service to the decision to purchase an insurance policy at PT. The Krishna Pratama Monument in Bengkulu City. The analytical method used is the validity test, reliability test, Multiple linear regression, coefficient of determination, F test and t test. Based on the research results indicate that Promotion (X1) partially has a significant effect on the purchase decision of an insurance policy at PT. Tugu Kresna Pratama Bengkulu City (Y) because the significant value is 0.046 < 0.05. Service quality (X2) partially has a significant effect on the purchase decision of an insurance policy at PT. Tugu Kresna Pratama Bengkulu City (Y) because the significant value is 0.000 < 0.05. Promotion variable (X1), service quality (X2) simultaneously or together have a significant effect on the purchase decision of an insurance policy at PT. Tugu Kresna Pratama Bengkulu City because the significant value is 0.000 < 0.05